Revisiting the Evolution of Mycobacterium bovis - Mostowy, Serge (American Society for Microbiology, 2005)
Though careful consideration has been placed towards genetic characterization of tubercle bacillus isolates causing disease in humans, those causing disease predominantly among wild and domesticated mammals have received less attention. In contrast to Mycobacterium tuberculosis, whose host range is largely specific to humans, M. bovis and “M bovis-like” organisms infect a broad range of animal species beyond their most prominent host in cattle. To determine whether strains of variable genomic content are associated with distinct distributions of disease, the DNA contents of M. bovis or M. bovis-like isolates from a variety of hosts were investigated via Affymetrix GeneChip. Consistent with previous genomic analysis of the M. tuberculosis complex (MTC), large sequence polymorphisms of putative diagnostic and biological consequence were able to unambiguously distinguish interrogated isolates. The distribution of deleted regions indicates organisms genomically removed from M. bovis and also points to structured genomic variability within M. bovis. Certain genomic profiles spanned a variety of hosts but were clustered by geography, while others associated primarily with host type. In contrast to the prevailing assumption that M. bovis has broad host capacity, genomic profiles suggest that distinct MTC lineages differentially infect a variety of mammals. From this, a phylogenetic stratification of genotypes offers a predictive framework upon which to base future genetic and phenotypic studies of the MTC.